Determining the minimum number of passive stretches necessary to alter musculotendinous stiffness - Ryan, E. D.; Herda, T. J.; Costa, P. B.; Defreitas, J. M.; Beck, T. W.; Stout, J.; Cramer, J. T. (Journal of Sports Sciences, 2009)
In this study, we examined the minimum number of constant-torque passive stretches necessary to reduce musculotendinous stiffness. Thirteen healthy individuals (mean age 22 years, s = 3; stature 1.67 m, s = 0.1; mass 66 kg, s = 13 kg) volunteered to participate in the investigation and underwent four 30-s constant-torque passive stretches of the plantar flexor muscles. Musculotendinous stiffness was examined from the angle-torque curves generated prior to the passive stretches, at the beginning of each 30-s stretch, and immediately following the four 30-s passive stretches. The results indicated that musculotendinous stiffness of the plantar flexors was reduced following two 30-s constant-torque passive stretches (P < 0.05) compared with the pre- musculotendinous stiffness assessment. Musculotendinous stiffness remained depressed following the third and fourth stretches, but did not decrease further. These findings suggest that two 30-s bouts of constant-torque passive stretching may be necessary to cause a significant decrease in musculotendinous stiffness of the plantar flexor muscles.